2005
DOI: 10.3171/sup.2005.102.s_supplement.0034
|View full text |Cite
|
Sign up to set email alerts
|

Long-term complications after gamma knife surgery for arteriovenous malformations

Abstract: Object. The authors analyzed of the long-term complications that occur 2 or more years after gamma knife surgery (GKS) for intracranial arteriovenous malformations (AVMs). Methods. Patients with previously untreated intracranial AVMs that were managed by GKS and followed for at least 2 years after treatment were selected for analysis (237 cases). Complete AVM obliteration was attained in 130 cases (54.9%), and incomplete obliteration in 107 cases (45.1%). Long-term complications were observed in 22 patients (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 9 publications
2
51
0
Order By: Relevance
“…The obliteration rate and the percentage of satisfactory vs. less satisfactory outcomes reported in the present study generally correspond to the results in other recently published studies (9,10,13,17,18,21,22). Complete AVM occlusion was obtained in 80% of our patients, which is a relatively high figure compared with other reports.…”
Section: Follow-upsupporting
confidence: 93%
See 2 more Smart Citations
“…The obliteration rate and the percentage of satisfactory vs. less satisfactory outcomes reported in the present study generally correspond to the results in other recently published studies (9,10,13,17,18,21,22). Complete AVM occlusion was obtained in 80% of our patients, which is a relatively high figure compared with other reports.…”
Section: Follow-upsupporting
confidence: 93%
“…Complications following radiation therapy typically occur as late events. Thus, inclusion of patients with a shorter follow-up period would give a falsely low incidence of radiation-related complications, because these often occur beyond 1 year after treatment (13). It has been reported that 82% of complications occur within the first 2 years and 92% within 3 years after treatment (15).…”
Section: Follow-upmentioning
confidence: 98%
See 1 more Smart Citation
“…This is comparable to other reported rates of symptomatic and asymptomatic parenchymal changes on follow-up MR images after radiosurgery [25,37,41,43], suggesting that only in a small percentage these radiological changes result in neurological signs or symptoms, although long term data are to be awaited. It has been suggested that delayed cyst formation is associated with a higher maximal treatment dose, a larger bAVMvolume, complete nidus obliteration, and a lobar location of the bAVM [15]. While our series is too small to investigate long-term radiation-induced toxicity, it is interesting to note that in the case in which neurological damage due to radiation toxicity was seen, the bAVMvolume was relatively large, with a deep, non-cortical location, and therefore a bAVM-score larger than 2.…”
Section: ■ Complications: Radiation-induced Neurological Deficits Andmentioning
confidence: 99%
“…There are some high-grade (Spetzler-Martin grade [4][5] AVMs that have no chance for surgical resection or endovascular treatment and where only stereotactic radiosurgical procedures such as GKS can be considered. So far, in addition to the obliteration rate of the nidus, quite a lot of cases that developed radiation injury such as perinidal edema or cyst formation after stereotactic radiosurgery have been reported.…”
mentioning
confidence: 99%